Availability of resources and acquisition of assistive technology by school managers in the state of Paraná - Freitas, Flaviane Pelloso Molina [UNESP]; de Oliveira, Jáima Pinheiro [UNESP]; Freitas, Carlos Cesar Garcia (My University, 2018)
The use of Assistive Technology in education becomes an instrument that favors the inclusion. Like this,it was aimed to identify in the state of Paraná, which existing programs allow the school manager to raise financial resources for the acquisition of Assistive Technology. A qualitative research was carried out, of documentary character, with search in the official sites of education of the state. The research demonstrated the existence of seven programs that met the requirement although they have demonstrated the existence of a large bureaucracy to be fulfilled.
Disponibilidade de recursos e aquisição de tecnologia assistiva pelos gestores escolares no estado do Paraná (Brasil)
Keywords: Assistive Technology; Inclusion; School manager